2008
DOI: 10.1097/jcp.0b013e3181603f5a
|View full text |Cite
|
Sign up to set email alerts
|

RGS4 Polymorphisms Predict Clinical Manifestations and Responses to Risperidone Treatment in Patients With Schizophrenia

Abstract: These findings suggest that RGS4 variances influence clinical manifestations of schizophrenia as well as the treatment response to risperidone, suggesting that RGS4 plays a role in the fundamental process of disease pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Rgs16 is involved in the regulation of circadian rhythms and in the regulation of islet survival and development of diabetes (13,45). Genetic variations in the Rgs4 gene are related to schizophrenia and mood disorders (16,22,37). As WS patients suffer from psychiatric disorders and from diabetes, the RGS pathway seems to be a biologically relevant target, based on our findings.…”
Section: Discussionmentioning
confidence: 70%
“…Rgs16 is involved in the regulation of circadian rhythms and in the regulation of islet survival and development of diabetes (13,45). Genetic variations in the Rgs4 gene are related to schizophrenia and mood disorders (16,22,37). As WS patients suffer from psychiatric disorders and from diabetes, the RGS pathway seems to be a biologically relevant target, based on our findings.…”
Section: Discussionmentioning
confidence: 70%
“…In a nonbiased gene array study, RGS4 was the most consistently altered transcript in the PFC of schizophrenia patients (Mirnics et al 2001). A postmortem study found significantly lower RGS4 mRNA and protein levels in the dlPFC of schizophrenia patients compared with healthy controls (Erdely et al 2006), and RGS4 SNPs predicted poorer performance on clinical ratings scales in a recent study performed in a population of Han-Chinese schizophrenia patients (Lane et al 2008). Reduced RGS4 in the dlPFC would lead to excessive protein kinase C signaling and impaired PFC cognitive function.…”
Section: Rgs4mentioning
confidence: 99%
“…Reduced RGS4 in the dlPFC would lead to excessive protein kinase C signaling and impaired PFC cognitive function. These patients also responded best to risperidone (Lane et al 2008), which reduces PI signaling by blocking extracellular receptors coupled to Gq (see below).…”
Section: Rgs4mentioning
confidence: 99%
“…However, subsequent findings support a role for RGS4 in both symptomology and pathophysiology. For example, a postmortem study found significantly lower mRNA and protein levels in the dlPFC of schizophrenia patients compared with healthy controls (Erdely et al 2006), and RGS4 SNPs predicted poorer performance on clinical ratings scales in a recent study performed in a population of Han-Chinese schizophrenia patients (Lane et al 2008).…”
Section: Rgs4mentioning
confidence: 99%